(untitled) (Research, Society and Development, 2022)
This study aims to describe the current scenario of primary care for pregnant and postpartum women in the prison system. The referring research project was a study in which an integrative literature review was carried out, made use of a qualitative approach, of a descriptive nature, the search and location of data was carried out in the databases: Scientific Electronic Librany Online and Biblioteca in Health, the inclusion criteria for the selection of articles will be: Complete articles from 2016 to 2022 available in Portuguese and foreign languages, the validated Ursi instrument was used for data collection, Methods and data analysis were performed through the Bardin’s method (2011). During the research of articles from 2016 to 2022, a deficit of current articles on the subject in question was noticed, given its importance in the qualification of professionals and information to the population. Articles from 2016 show how pregnant and postpartum women experience pregnancy in prison, while the most current articles from 2018 to 2022 address strategies for improving the pregnancy and postpartum process in prison to be less painful among inmates. The study made it possible to know and understand how pregnant and postpartum women are treated as pregnant women and are treated and cared for, according to SUS guidelines and legislation laws.